Composite microsphere, anisotropic conductive film and preparation method of anisotropic conductive film

By preparing Ni@PS composite microspheres and using modified adhesives and dispersants, the adhesion and dispersion of the microspheres and substrates in the conductive film are solved, the tensile and conductive properties of the conductive film are improved, and the mechanical strength and durability are achieved.

CN120376216APending Publication Date: 2025-07-25ZHEJIANG FULAI NEW MATERIAL CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510542895.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The lack of adhesion and poor dispersion between the composite microspheres and the matrix material in traditional conductive films affects the conductivity and mechanical stability, and the prior art improvement methods have limitations.

Method used

By preparing Ni@PS composite microspheres, and using modified adhesives and modified dispersants, combined with specific process steps, the bonding strength and dispersion of the microspheres and substrate are improved to form an interpenetrating network structure.

Benefits of technology

The tensile and conductive properties of the conductive film are significantly improved, the adhesion between the conductive film and the substrate is enhanced, and the overall mechanical strength and durability of the conductive film are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a composite microsphere, an anisotropic conductive film and a preparation method of the anisotropic conductive film, and belongs to the technical field of conductive films. The conductive film comprises the following raw materials in parts by weight: 60-80 parts of epoxy acrylate resin, 12-15 parts of a modified adhesive, 10-30 parts of composite microspheres, 1-3 parts of a coupling agent, 0.5-1 part of a modified dispersant and 10-30 parts of toluene, the preparation method comprises the following steps: firstly, reacting 1, 3-bis ((2, 2-dimethyl-1, 3-dioxolane-4-yl) methoxy) propan-2-amine with methacryloyl chloride to generate an amide product; reacting the pentaerythritol tetra (3-mercaptopropionic acid) ester with the amide product to generate an eight-arm cyclopentane compound, and hydrolyzing the eight-arm cyclopentane compound to generate an eight-arm hydroxyl compound; the cassava starch is hydrolyzed to generate hydrolyzed starch, and then the hydrolyzed starch reacts with the eight-arm hydroxyl compound to generate the modified adhesive. The anisotropic conductive film prepared by the invention has good tensile property and conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive films, and particularly relates to a composite microsphere, an anisotropic conductive film and a preparation method thereof. Background Art

[0002] With the rapid development of electronic technology, the demand for conductive films in the fields of electronic packaging, flexible electronic devices, etc. is increasing continuously. However, in the preparation process of traditional conductive films, problems such as insufficient adhesion between composite microspheres and matrix materials and poor dispersion of microspheres have always been the key technical bottlenecks restricting the improvement of their performance. For example, in an anisotropic conductive film (ACF), the dispersion of conductive microspheres and the adhesion to the resin matrix directly affect the conductive performance and mechanical stability. In the prior art, conductive microspheres are prone to elastic deformation during the hot pressing process, resulting in an increase in the contact resistance with the electrodes, thereby affecting the long-term reliability of the conductive film. In addition, the interfacial bonding force between the metal coating on the surface of the microspheres and the polymer core is weak and is prone to peeling off during processing or use, further reducing the performance of the conductive film.

[0003] To solve these problems, researchers have tried to improve the dispersion and adhesion of composite microspheres through various methods. For example, through a two-step treatment method on the surface of the microspheres, composite conductive microspheres with a dense coating, high dispersion and good conductivity have been successfully prepared, significantly reducing the contact resistance of the conductive film. In addition, electroless plating is used to form a uniform metal layer on the surface of the microspheres, and rare earth elements or stabilizers are introduced, which not only improves the density and conductivity of the coating, but also improves the dispersion of the microspheres. However, these methods still have certain limitations, such as insufficient universality for different matrix materials or complex preparation processes. Therefore, developing a new technology that can effectively solve the problems of insufficient adhesion and poor dispersion between composite microspheres and the conductive film matrix is of great significance for improving the overall performance and application range of conductive films.

[0004] Chinese Patent Invention No. CN102136314A discloses a preparation method of a composite microsphere, an anisotropic conductive material and an anisotropic conductive film, including preparing a polymer core and at least one metal conductive layer, and at least one functional part is also provided between the core and the metal conductive layer, and the functional part is composed of a polymer and has a functional group; this invention solves the problems that the metal conductive layer of the composite microsphere is prone to cracking, wrinkling, etc., but the dispersion of the composite microsphere in the conductive film is poor. Summary of the Invention

[0005] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide a composite microsphere, an anisotropic conductive film and a preparation method thereof.

[0006] To achieve the above purpose, the present invention is realized through the following technical solutions: A composite microsphere is prepared by the following method: (1) Under nitrogen protection, styrene monomer reacts under the action of potassium persulfate and sodium dodecyl sulfonate to obtain monodisperse PS microspheres; (2) The PS microspheres are immersed in concentrated sulfuric acid and stirred for sulfonation, and then ultrasonically activated with an amino silane coupling agent in absolute ethanol to obtain activated PS microspheres; (3) An electroplating solution containing nickel sulfate, sodium hypophosphite, and sodium citrate is mixed with the activated PS microspheres, and ultrasonic electroplating is carried out to obtain Ni@PS composite microspheres.

[0007] An anisotropic conductive film comprises raw materials in the following parts by weight: 60 - 80 parts of epoxy acrylate resin, 12 - 15 parts of modified adhesive, 10 - 30 parts of Ni@PS composite microspheres, 1 - 3 parts of coupling agent, 0.5 - 1 part of modified dispersant, and 10 - 30 parts of toluene; The modified adhesive is prepared by the following method: S1: Under nitrogen protection, 1,3 - bis((2,2 - dimethyl - 1,3 - dioxolan - 4 - yl)methoxy)propan - 2 - amine reacts with methacryloyl chloride under the action of triethylamine to form an amide product; S2: Pentaerythritol tetra(3 - mercaptopropionate) reacts with the amide product under the action of initiator AIBN to form an octa - arm cyclopentane compound, and the octa - arm cyclopentane compound is hydrolyzed to form an octa - arm hydroxyl compound; S3: Cassava starch forms hydrolyzed starch under formic acid conditions, and then the hydrolyzed starch reacts with the octa - arm hydroxyl compound to form a modified adhesive.

[0008] In step S1, the feeding mass ratio of 1,3 - bis((2,2 - dimethyl - 1,3 - dioxolan - 4 - yl)methoxy)propan - 2 - amine to methacryloyl chloride is 3:(10 - 12).

[0009] In step S2, the feeding mass ratio of pentaerythritol tetra(3 - mercaptopropionate) to the amide product is 5:(12 - 16).

[0010] In step S3, the feeding mass ratio of cassava starch to the octa - arm hydroxyl compound is (10 - 12):(6 - 8).

[0011] The coupling agent is one of 3 - aminopropyltriethoxysilane and 3 - aminopropyltrimethoxysilane.

[0012] The modified dispersant is prepared by the following method: S1: Under nitrogen protection, 2 - amino - 4 - (4 - chlorophenyl)thiazole is slowly added to a tetrahydrofuran solution of chloropropene magnesium, and the reaction is carried out for 4 - 8 h to obtain a double - bond compound; S2: Under nitrogen protection, 3-glycidoxypropyltrimethoxysilane reacts with a double-bond compound to obtain a silylated product; S3: The silylated product, acrylic acid, and allyloxy polyoxyethylene ether react under the action of ammonium persulfate to form a modified dispersant.

[0013] In step S1, the molar ratio of the magnesium allyl chloride to 2-amino-4-(4-chlorophenyl)thiazole in the feed is (1.2 - 1.5):1; the concentration of the magnesium allyl chloride solution in tetrahydrofuran is 0.5 mol / L.

[0014] In step S2, the mass ratio of the 3-glycidoxypropyltrimethoxysilane to the double-bond compound in the feed is (10 - 12):5; In step S3, the mass ratio of the silylated product, acrylic acid, and allyloxy polyoxyethylene ether in the feed is 5:(10 - 15):(5 - 7).

[0015] A method for preparing an anisotropic conductive film includes the following steps: (1) Weigh by weight: 60 - 80 parts of epoxy acrylate resin, 12 - 15 parts of modified adhesive, 10 - 30 parts of Ni@PS composite microspheres, 1 - 3 parts of coupling agent, 0.5 - 1 part of modified dispersant, and 10 - 30 parts of toluene; (2) Add the composite microspheres and the coupling agent to an anhydrous ethanol solution, ultrasonically disperse for 30 min, and vacuum dry at 60°C for 2 h to obtain modified composite microspheres; then, after high-speed shear mixing and grinding with a three-roll mill in sequence for the epoxy acrylate resin, modified adhesive, and toluene, add the modified composite microspheres and the modified dispersant, and mix evenly using a planetary stirrer to obtain a slurry; (3) Use a slot coater to evenly coat the slurry on a PET release film; pre-bake at 80°C for 5 min to form a semi-cured film; place the semi-cured film in a vertical magnetic field to align the composite microspheres in the Z-axis direction; (4) Finally, perform stepwise curing: The first stage: cure at 100°C for 30 min; the second stage: cure at 150°C for 60 min. After curing, peel off the release film to obtain the anisotropic conductive film.

[0016] Due to the above technical solutions, the beneficial effects of the present invention include: (1) This application prepares a novel Ni@PS composite microsphere for anisotropic conductive films.

[0017] (2) First, in the present invention, an amide product is formed by an affinity substitution reaction between the amino group in 1,3-bis((2,2-dimethyl-1,3-dioxolan-4-yl)methoxy)propan-2-amine and the acyl chloride group in methacryloyl chloride under the action of triethylamine; the thiol group in pentaerythritol tetra(3-mercaptopropionate) reacts with the carbon-carbon double bond in the amide product through a thiol-ene click reaction to form an octaradial cyclopentane compound, and the octaradial cyclopentane compound is hydrolyzed to form an octaradial hydroxy compound; cassava starch is hydrolyzed to form hydrolyzed starch, and then the hydrolyzed starch reacts with the octaradial hydroxy compound to form a modified adhesive.

[0018] (3) The modified adhesive synthesized by synthesizing an octaradial cyclopentane compound and reacting it with hydrolyzed starch has excellent adhesion performance. Since more hydroxyl groups are exposed after the hydrolysis of cassava starch, it can form a rigid-flexible interpenetrating network with the octaradial hydroxy compound through hydrogen bonds and physical entanglement, improving the flexibility of the adhesive and enhancing the bonding strength between the adhesive and the substrate.

[0019] (4) In the present invention, a double-bond compound is obtained by reacting magnesium allyl chloride with 2-amino-4-(4-chlorophenyl)thiazole; then, a silylated product is obtained by reacting 3-glycidoxypropyltrimethoxysilane with the double-bond compound; the silylated product, acrylic acid, and allyloxypolyoxyethylene ether react to form a modified dispersant.

[0020] (5) The modified dispersant can uniformly disperse the conductive filler and reduce the agglomeration phenomenon, thereby significantly reducing the resistance of the conductive film; the silylated product formed by reacting 3-glycidoxypropyltrimethoxysilane with the double-bond compound can form chemical bonds with the substrate surface, thereby significantly improving the adhesion between the conductive film and the substrate. The cross-linked network formed by the silylated product, acrylic acid, and allyloxypolyoxyethylene ether under the action of ammonium persulfate improves the overall mechanical strength and durability of the conductive film. Specific Embodiments

[0021] The following is further described in conjunction with embodiments, but the present invention is not limited to these embodiments.

[0022] Example 1 Preparation of Composite Microspheres: Preparation of PS Microspheres: Potassium persulfate, sodium dodecylsulfonate, and 50 g of styrene monomer were added to 1000 ml of an ethanol / water mixed solvent (volume ratio 1:4). The final concentration of potassium persulfate in the system was 0.2 mol / L, and the final concentration of sodium dodecylsulfonate in the system was 0.1 mol / L; under nitrogen protection, the reaction was carried out at 75 °C for 7 hours to obtain monodisperse PS microspheres with a particle size of 2 μm (DN98).

[0023] Surface treatment of microspheres: Immerse PS microspheres in 98% concentrated sulfuric acid and stir at 50 °C for sulfonation for 30 minutes to introduce sulfonic acid groups to enhance surface activity. Adopt an activation process, ultrasonically treat the sulfonated microspheres and an amino silane coupling agent (APTMS) in absolute ethanol for 2 hours to graft amino functional groups on the surface and obtain activated PS microspheres.

[0024] Preparation of electroless nickel plating solution: Dissolve nickel sulfate, sodium hypophosphite, and sodium citrate in deionized water. The final concentrations are 20 g / L for nickel sulfate, 25 g / L for sodium hypophosphite, and 15 g / L for sodium citrate. Adjust the pH to 9.0 - 9.5 with ammonia water to obtain the electroplating solution.

[0025] Electroplating: Mix the electroplating solution and the activated PS microspheres (mixing mass ratio 10:1), react at a constant temperature of 85 °C for 50 minutes under ultrasonic assistance, wash by centrifugation with deionized water, and then dry in vacuum at 60 °C for 12 hours to obtain Ni@PS composite microspheres.

[0026] Example 2 Preparation of modified adhesive: S1: Under nitrogen protection, add 500 g of dichloromethane, 30 g of 1,3-bis((2,2-dimethyl-1,3-dioxolan-4-yl)methoxy)propan-2-amine, and 18 g of catalyst triethylamine to the reactor, stir and mix evenly. Under an ice bath, slowly add 100 g of methacryloyl chloride, dropwise add for 20 min, raise the temperature to room temperature after dropping, react for 8 h, then filter, carry out vacuum distillation at 40 °C for 1 h, and then wash three times with saturated sodium chloride solution (200 ml of saturated sodium chloride solution is used each time), and dry in vacuum at 50 °C for 5 h to obtain an amide product; the reaction equation is shown as follows: ; S2: Under nitrogen protection, add 800 g of DMSO, 50 g of pentaerythritol tetra(3-mercaptopropionate), 120 g of amide product to the reactor, stir and mix evenly, raise the temperature to 80 °C, then add 14 g of initiator AIBN, react for 24 h, carry out vacuum distillation at 60 °C for 3 h, and obtain an octa-armed cyclopentane compound by silica gel column separation; add 500 g of deionized water and 80 g of octa-armed cyclopentane compound to the reactor, then add 60 g of 3 wt% dilute hydrochloric acid, stir and mix evenly, raise the temperature to reflux and react for 2 h, then add 10 wt% sodium hydroxide solution to adjust the pH to neutral, carry out vacuum distillation at 60 °C for 3 h, and dry in vacuum at 60 °C for 5 h to obtain an octa-armed hydroxyl compound; the reaction equation is shown as follows: ; The nuclear magnetic resonance hydrogen spectrum data are as follows: 11H NMR (500 MHz, Chloroform-d) δ 6.37 (d, J = 9.8 Hz, 4H), 4.14 (s,8H), 3.85 – 3.65 (m, 36H), 3.53 – 3.40 (m, 24H), 3.22 (t, J = 5.7 Hz, 8H),3.11 (d, J = 6.3 Hz, 8H), 2.97 (dd, J = 13.9, 5.3 Hz, 4H), 2.92 – 2.78 (m,8H), 2.75 – 2.60 (m, 8H), 2.56 – 2.50 (m, 8H), 1.13 (d, J = 6.6 Hz, 12H). S3: Add 300 g of deionized water, 100 g of tapioca starch, and 3 g of formic acid into the reactor, stir and mix evenly, heat up to 80 °C and react for 1 h to obtain a hydrolyzed starch solution; under nitrogen protection, add 240 g of deionized water and 60 g of octa-armed hydroxy compound into the reactor, stir and mix evenly, heat up to 90 °C, keep warm for 2 h, cool down to 50 °C, add the hydrolyzed starch solution (all of the above-prepared is added), after reacting for 3 h, cool to room temperature to obtain a modified adhesive.

[0027] Example 3 Preparation of the modified adhesive: S1: Under nitrogen protection, add 500 g of dichloromethane, 30 g of 1,3-bis((2,2-dimethyl-1,3-dioxolan-4-yl)methoxy)propan-2-amine, and 18 g of catalyst triethylamine into the reactor, stir and mix evenly, under an ice bath, slowly add 110 g of methacryloyl chloride, dropwise add for 20 min, after dropping, raise the temperature to room temperature, after reacting for 6 h, filter, carry out reduced pressure distillation at 40 °C for 1 h, then wash three times with saturated sodium chloride solution (200 ml of saturated sodium chloride solution is used each time), and carry out vacuum drying at 45 °C for 5 h to obtain an amide product; S2: Under nitrogen protection, add 800 g of DMSO, 50 g of pentaerythritol tetra(3-mercaptopropionate), 140 g of amide product into the reactor, stir and mix evenly, heat up to 90 °C, then add 14 g of initiator AIBN, after reacting for 22 h, carry out reduced pressure distillation at 70 °C for 2 h, and obtain an octa-armed cyclopentane compound by silica gel column separation; add 500 g of deionized water and 80 g of octa-armed cyclopentane compound into the reactor, then add 60 g of 3 wt% dilute hydrochloric acid, stir and mix evenly, heat up to reflux and react for 2 h, add 10 wt% sodium hydroxide solution to adjust the pH to neutral, carry out reduced pressure distillation at 60 °C for 3 h, and carry out vacuum drying at 60 °C for 6 h to obtain an octa-armed hydroxy compound; S3: Add 350 g of deionized water, 110 g of tapioca starch, and 3 g of formic acid into the reactor, stir and mix evenly, heat up to 85 °C and react for 45 min to obtain a hydrolyzed starch solution; under nitrogen protection, add 280 g of deionized water and 70 g of octa-arm hydroxy compound into the reactor, stir and mix evenly, heat up to 100 °C, keep warm for 1 h, cool down to 50 °C, add the hydrolyzed starch solution (all the above-prepared solution is added), continue to react for 2 h, and then cool to room temperature to obtain the modified adhesive.

[0028] Example 4 Preparation of modified adhesive: S1: Under nitrogen protection, add 500 g of dichloromethane, 30 g of 1,3-bis((2,2-dimethyl-1,3-dioxolan-4-yl)methoxy)propan-2-amine and 18 g of catalyst triethylamine into the reactor, stir and mix evenly. Under ice bath, slowly add 120 g of methacryloyl chloride dropwise for 20 min. After dropping, raise the temperature to room temperature and react for 5 h. Then filter, carry out reduced pressure distillation at 40 °C for 1.5 h, and then wash three times with saturated sodium chloride solution (200 ml of saturated sodium chloride solution is used each time), and carry out vacuum drying at 45 °C for 5 h to obtain the amide product; S2: Under nitrogen protection, add 800 g of DMSO, 50 g of pentaerythritol tetra(3-mercaptopropionate), and 160 g of amide product into the reactor, stir and mix evenly, heat up to 100 °C, and then add 14 g of initiator AIBN. After reacting for 20 h, carry out reduced pressure distillation at 50 °C for 3 h, and separate through a silica gel column to obtain an octa-arm cyclopentane compound; add 500 g of deionized water and 80 g of octa-arm cyclopentane compound into the reactor, then add 60 g of 3 wt% dilute hydrochloric acid, stir and mix evenly, heat up to reflux and react for 2 h, then add 10 wt% sodium hydroxide solution to adjust the pH to neutral, carry out reduced pressure distillation at 60 °C for 3 h, and carry out vacuum drying at 70 °C for 5 h to obtain an octa-arm hydroxy compound; S3: Add 380 g of deionized water, 120 g of tapioca starch, and 3 g of formic acid into the reactor, stir and mix evenly, heat up to 90 °C and react for 30 min to obtain a hydrolyzed starch solution; under nitrogen protection, add 320 g of deionized water and 80 g of octa-arm hydroxy compound into the reactor, stir and mix evenly, heat up to 100 °C, keep warm for 1 h, cool down to 50 °C, add the hydrolyzed starch solution (all the above-prepared solution is added), continue to react for 1 h, and then cool to room temperature to obtain the modified adhesive.

[0029] Example 5 Preparation of modified dispersant: S1: Under an ice bath, 0.1 mol of 2-amino-4-(4-chlorophenyl)thiazole (0.05 mol per batch, with a 20-min interval between batches) was added portionwise to 240 ml of a 0.5 mol / L solution of allylmagnesium chloride in tetrahydrofuran. After reacting for 20 h, 250 ml of saturated ammonium chloride solution was added, and the mixture was stirred evenly. It was allowed to stand for liquid separation at 0 °C. The organic phase was dried with 50 g of anhydrous sodium sulfate for 2 h and then distilled under reduced pressure at 60 °C for 3 h to obtain a double-bond compound; S2: Under nitrogen protection, 500 g of anhydrous methanol, 50 g of the double-bond compound were added to a reactor and stirred evenly. The temperature was raised to 60 °C, and then 100 g of 3-glycidoxypropyltrimethoxysilane was slowly added dropwise over 20 min. After reacting for 24 h, it was cooled to room temperature and distilled under reduced pressure at 40 °C for 2 h to obtain a silylated product. The 1H NMR data are as follows: 1 H NMR (500 MHz, Chloroform- d ) δ 7.72 – 7.66 (m, 2H), 7.34 – 7.27 (m, 2H), 7.09 (s, 1H), 5.74(ddt, J = 17.1, 9.7, 7.5 Hz, 1H), 5.19 (ddt, J = 9.7, 2.2, 1.5 Hz, 1H), 4.98(ddt, J = 17.0, 2.2, 1.5 Hz, 1H), 4.02 (qt, J = 6.6, 5.5 Hz, 2H), 3.91 – 3.83(m, 4H), 3.76 – 3.69 (m, 2H), 3.62 (dd, J = 13.3, 6.6 Hz, 2H), 3.59 (s, 18H),3.51 – 3.36 (m, 6H), 3.31 (dtt, J = 7.5, 1.6, 0.8 Hz, 2H), 1.71 – 1.60 (m,4H), 0.75 (t, J = 9.8 Hz, 4H). S3: Under nitrogen protection, 2000 g of deionized water, 100 g of acrylic acid, 50 g of allyloxypolyoxyethylene ether, and 50 g of the silylated product were added to a reactor and stirred evenly. The temperature was raised to 80 °C, and then 15 g of ammonium persulfate was added. After reacting for 3 h, 5000 ml of anhydrous ethanol was added, and the mixture was stirred for 20 min, allowed to stand for 1 h, filtered by suction, and dried in vacuo at 60 °C for 4 h to obtain a modified dispersant.

[0030] Example 6 Preparation of the modified dispersant: S1: Under an ice bath, slowly add 0.1 mol of 2-amino-4-(4-chlorophenyl)thiazole (0.05 mol per batch, with a 20-minute interval between batches) dropwise to 260 ml of a 0.5 mol / L solution of allylmagnesium chloride in tetrahydrofuran. After reacting for 22 h, add 250 ml of saturated ammonium chloride solution, mix evenly, let it stand for layer separation at 0 °C, dry the organic phase with 50 g of anhydrous sodium sulfate for 2 h, and perform vacuum distillation at 70 °C for 2 h to obtain a double-bond compound; S2: Under nitrogen protection, add 500 g of anhydrous methanol and 50 g of the double-bond compound to a reactor, stir and mix evenly, heat up to 70 °C, and then slowly add 110 g of 3-glycidoxypropyltrimethoxysilane dropwise over 20 min. After reacting for 22 h, cool to room temperature and perform vacuum distillation at 50 °C for 2 h to obtain a silylated product; S3: Under nitrogen protection, add 2000 g of deionized water, 120 g of acrylic acid, 60 g of allyloxypolyoxyethylene ether, and 50 g of the silylated product to a reactor, stir and mix evenly, heat up to 80 °C, and then add 15 g of ammonium persulfate. After reacting for 4 h, add 5000 ml of anhydrous ethanol, stir for 20 min, let it stand for 1 h, perform suction filtration, and dry under vacuum at 70 °C for 3 h to obtain a modified dispersant.

[0031] Example 7 Preparation of modified dispersant: S1: Under an ice bath, slowly add 0.1 mol of 2-amino-4-(4-chlorophenyl)thiazole (0.05 mol per batch, with a 20-minute interval between batches) dropwise to 300 ml of a 0.5 mol / L solution of allylmagnesium chloride in tetrahydrofuran. After reacting for 24 h, add 250 ml of saturated ammonium chloride solution, mix evenly, let it stand for layer separation at 0 °C, dry the organic phase with 50 g of anhydrous sodium sulfate for 2 h, and perform vacuum distillation at 80 °C for 1 h to obtain a double-bond compound; S2: Under nitrogen protection, add 500 g of anhydrous methanol and 50 g of the double-bond compound to a reactor, stir and mix evenly, heat up to 80 °C, and then slowly add 120 g of 3-glycidoxypropyltrimethoxysilane dropwise over 20 min. After reacting for 20 h, cool to room temperature and perform vacuum distillation at 60 °C for 45 min to obtain a silylated product; S3: Under nitrogen protection, add 2000 g of deionized water, 150 g of acrylic acid, 70 g of allyloxypolyoxyethylene ether, and 50 g of the silylated product to a reactor, stir and mix evenly, heat up to 85 °C, and then add 20 g of ammonium persulfate. After reacting for 2 h, add 5000 ml of anhydrous ethanol, stir for 20 min, let it stand for 1 h, perform suction filtration, and dry under vacuum at 50 °C for 5 h to obtain a modified dispersant.

[0032] Example 8 Preparation of anisotropic conductive film: (1) Weigh: 600 g of epoxy acrylate resin, 120 g of modified adhesive (prepared in Example 2), 100 g of composite microspheres (prepared in Example 1), 5 g of modified dispersant (prepared in Example 5), 10 g of coupling agent (3-aminopropyltriethoxysilane), and 100 g of toluene; (2) Add the composite microspheres and the coupling agent to 1000 ml of anhydrous ethanol solution, ultrasonically disperse (power: 300 W) for 30 min, and vacuum dry at 60 °C for 2 h to obtain modified composite microspheres; successively carry out high-speed shear mixing on the epoxy acrylate resin, modified adhesive, and toluene at a rotation speed of 2000 rpm for 30 min, then place it in a three-roll mill and grind twice with a roll gap of 5 μm; finally, add the modified composite microspheres and the modified dispersant, and mix evenly with a planetary stirrer at a revolution speed of 2000 rpm and a rotation speed of 500 rpm for 20 min to obtain a slurry; (3) Use a slot coater (coating speed: 5 m / min, gap height: 50 μm) to evenly coat the slurry on a PET release film; pre-bake at 80 °C for 5 min to form a semi-cured film; place the semi-cured film in a vertical magnetic field (magnetic field strength: 0.5 T, time: 10 min) to align the composite microspheres in the Z-axis direction; (4) Finally, carry out stepwise curing: The first stage: cure at 100 °C for 30 min; The second stage: cure at 150 °C for 60 min. After curing, peel off the release film to obtain an anisotropic conductive film of composite microspheres with a thickness of 15 μm.

[0033] Example 9 Preparation of anisotropic conductive film: (1) Weigh: 700 g of epoxy acrylate resin, 130 g of modified adhesive (prepared in Example 3), 200 g of composite microspheres (prepared in Example 1), 8 g of modified dispersant (prepared in Example 6), 20 g of coupling agent (3-aminopropyltrimethoxysilane), and 200 g of toluene; (2) Add the composite microspheres and the coupling agent to 1000 ml of anhydrous ethanol solution, ultrasonically disperse (power: 300 W) for 30 min, and vacuum dry at 60 °C for 2 h to obtain modified composite microspheres; successively carry out high-speed shear mixing on the epoxy acrylate resin, modified adhesive, and toluene at a rotation speed of 2000 rpm for 30 min, then place it in a three-roll mill and grind twice with a roll gap of 5 μm; finally, add the modified composite microspheres and the modified dispersant, and mix evenly with a planetary stirrer at a revolution speed of 2000 rpm and a rotation speed of 500 rpm for 20 min to obtain a slurry; (3) Use a slot coater (coating speed 5 m / min, gap height 50 μm) to evenly coat the slurry on a PET release film; pre-bake at 80 °C for 5 min to form a semi-cured film; place the semi-cured film in a vertical magnetic field (magnetic field strength 0.5 T, time 10 min) to align the composite microspheres along the Z-axis direction; (4) Finally, perform stepwise curing: The first stage: cure at 100 °C for 30 min; The second stage: cure at 150 °C for 60 min. After curing, peel off the release film to obtain an anisotropic conductive film with a thickness of 15 μm.

[0034] Example 10 Preparation of anisotropic conductive film: (1) Weigh: 800 g of epoxy acrylate resin, 150 g of modified adhesive (prepared in Example 4), 300 g of composite microspheres (prepared in Example 1), 10 g of modified dispersant (prepared in Example 7), 30 g of coupling agent (3-aminopropyltriethoxysilane), and 300 g of toluene; (2) Add the composite microspheres and the coupling agent to 1000 ml of anhydrous ethanol solution, ultrasonically disperse (power 300 W) for 30 min, and vacuum dry at 60 °C for 2 h to obtain modified composite microspheres; successively perform high-speed shear mixing on the epoxy acrylate resin, modified adhesive, and toluene at a rotation speed of 2000 rpm for 30 min, then grind twice with a three-roll mill with a roll gap of 5 μm; finally, add the modified composite microspheres and the modified dispersant, and mix evenly with a planetary stirrer at a revolution speed of 2000 rpm and a rotation speed of 500 rpm for 20 min to obtain a slurry; (3) Use a slot coater (coating speed 5 m / min, gap height 50 μm) to evenly coat the slurry on a PET release film; pre-bake at 80 °C for 5 min to form a semi-cured film; place the semi-cured film in a vertical magnetic field (magnetic field strength 0.5 T, time 10 min) to align the composite microspheres along the Z-axis direction; (4) Finally, perform stepwise curing: The first stage: cure at 100 °C for 30 min; The second stage: cure at 150 °C for 60 min. After curing, peel off the release film to obtain an anisotropic conductive film with a thickness of 15 μm.

[0035] Comparative Example 1 An anisotropic conductive film of composite microspheres, the raw material composition and process are basically the same as those in Example 9, the difference is that the modified adhesive is replaced with an equal weight of PU5215 polyurethane adhesive.

[0036] Comparative Example 2 An anisotropic conductive film of composite microspheres, the raw material composition and process are basically the same as those in Example 9, the difference is that the modified adhesive is replaced with an equal weight of modified adhesive prepared by the following method: The preparation method of the modified adhesive is basically the same as that of Example 3, except that 30 g of 1,3-bis((2,2-dimethyl-1,3-dioxolan-4-yl)methoxy)propan-2-amine in step S1 is replaced with an equal weight of 2,2-dimethyl-1,3-dioxolane-4-methanamine.

[0037] Comparative Example 3 A composite microsphere anisotropic conductive film has the same raw material composition and process as Example 9, except that the modified adhesive is replaced with an equal weight of a modified adhesive prepared by the following method: The preparation method of the modified adhesive is basically the same as that of Example 3, except that pentaerythritol tetra(3-mercaptopropionate) in step S2 is replaced with an equal weight of ethylene glycol bis(mercaptoacetate).

[0038] Comparative Example 4 A composite microsphere anisotropic conductive film has the same raw material composition and process as Example 9, except that the modified dispersant is replaced with an equal weight of polyvinyl alcohol (PVA-2499).

[0039] Comparative Example 5 A composite microsphere anisotropic conductive film has the same raw material composition and process as Example 9, except that the modified dispersant is replaced with an equal weight of a modified dispersant prepared by the following method: S1: Under ice bath, slowly add 0.1 mol of 2-amino-4-(4-chlorophenyl)thiazole (0.05 mol per batch, batch interval 20 min) to 260 ml of a 0.5 mol / L solution of allylmagnesium chloride in tetrahydrofuran. After reacting for 22 h, add 250 ml of saturated ammonium chloride solution, mix evenly, let it stand and separate layers at 0 °C. The organic phase is dried with 50 g of anhydrous sodium sulfate for 2 h, and distilled under reduced pressure at 70 °C for 2 h to obtain a double bond compound. S2: Under nitrogen protection, add 2000 g of deionized water, 120 g of acrylic acid, 60 g of allyloxy polyoxyethylene ether, and 50 g of the double bond compound to the reactor, stir and mix evenly, heat up to 80 °C, then add 15 g of ammonium persulfate. After reacting for 4 h, add 5000 ml of absolute ethanol, stir for 20 min, let it stand for 1 h, filter by suction, and dry under vacuum at 70 °C for 3 h to obtain the modified dispersant.

[0040] Comparative Example 6 A composite microsphere anisotropic conductive film has the same raw material composition and process as Example 9, except that the modified dispersant is replaced with an equal weight of a modified dispersant prepared by the following method: Under nitrogen protection, 2000 g of deionized water, 120 g of acrylic acid, 60 g of allyloxy polyoxyethylene ether, and 50 g of γ-methacryloxypropyltrimethoxysilane were added to the reactor, stirred and mixed evenly, heated to 80 °C, then 10 g of ammonium persulfate was added, and after reacting for 4 h, 5000 ml of absolute ethanol was added, stirred for 20 min, allowed to stand for 1 h, filtered by suction, and dried in vacuo at 70 °C for 3 h to obtain the modified dispersant.

[0041] Comparative Example 7 An anisotropic conductive film prepared by using the raw material composition, ratio and method of Example 22 of the Chinese invention patent with the publication number CN102136314A.

[0042] The materials used in the examples and comparative examples of this application are as follows unless otherwise specified: The epoxy acrylate resin model is JD-EA-165, purchased from Jiangsu Yangshi Chemical Research Institute Co., Ltd.; the PET release film model is JHS005, purchased from Shenzhen Jinhengcheng Technology Co., Ltd.; tapioca starch (CS), food grade, purchased from Guangxi Honghao Starch Development Co., Ltd.; the number average molecular weight of allyloxy polyoxyethylene ether is 1000.

[0043] The anisotropic conductive films prepared in Examples 8-10 and the comparative examples were subjected to a tensile strength test. The experimental method was based on the ASTM D638 standard, and the tensile speed was 50 mm / min; The anisotropic conductive films prepared in Examples 8-10 and the comparative examples were subjected to a through-conduction resistance performance test. The resistance value in the vertical direction was measured by the four-probe method, and the test results are shown in Table 1.

[0044] Table 1

[0045] It can be seen from Table 1 that the anisotropic conductive films prepared in Examples 8-10 have excellent tensile strength and conductive performance.

[0046] The modified adhesive added in Comparative Example 1 was a polyurethane adhesive with an equal weight. It can be seen from the data in Table 1 that the tensile strength was 40.55 MPa and the tensile strength was relatively low.

[0047] Comparative Example 2 and Comparative Example 3 are comparative examples different from Example 9. The difference is that in the preparation process of the modified adhesive, 1,3-bis((2,2-dimethyl-1,3-dioxolan-4-yl)methoxy)propan-2-amine in step S1 is replaced by 2,2-dimethyl-1,3-dioxolane-4-methanamine; in Comparative Example 3, pentaerythritol tetrakis(3-mercaptopropionate) in step S2 of the preparation process of the modified adhesive is replaced by ethylene glycol dimercaptoacetate. It can be seen from the data in Table 1 that the tensile strength is low and the electrical conductivity is poor. This is because in this application, through the reaction of pentaerythritol tetrakis(3-mercaptopropionate) with the amide product, a highly branched eight-arm structure is formed. This multi-arm design significantly increases the crosslinking sites, constructs a denser network, and endows the conductive film with higher tensile strength and creep resistance; when pentaerythritol tetrakis(3-mercaptopropionate) is replaced by ethylene glycol dimercaptoacetate, a four-arm structure is generated, and the crosslinking points of the four-arm cyclopentane are only 1 / 2 of those of the eight-arm, and the network is loose, resulting in lower mechanical strength and easy interfacial peeling due to stress concentration. At the same time, the free hydroxyl groups on the surface of the eight-arm hydroxy compound and the polar groups of the amide can form strong hydrogen bonds or coordination interactions with the conductive particles, inhibiting filler aggregation.

[0048] Comparative Example 4 is a comparative example different from Example 9. The difference is that the modified dispersant is replaced by polyvinyl alcohol. It can be seen from the data in Table 1 that both the tensile strength and the electrical conductivity are inferior to those of this application.

[0049] Comparative Example 5 is a comparative example different from Example 9. The difference is that no silanized product is added in the preparation process of the modified dispersant. It can be seen from the data in Table 1 that the tensile strength is average. This is because in step S2 of this application, 3-glycidoxypropyltrimethoxysilane reacts with the double-bond compound to open the epoxy ring, and the generated hydroxyl groups form hydrogen bonds with the surface of the microspheres, inhibiting interfacial peeling. The introduction of allyloxy polyoxyethylene ether endows the material with high toughness and can relieve stress concentration.

[0050] Comparative Example 6 is a comparative example different from Example 9. The difference is that the silanized product prepared in step S2 is replaced by γ-methacryloxypropyltrimethoxysilane. It can be seen from the data in Table 1 that the tensile strength is average. This is because the linear segments formed by γ-methacryloxypropyltrimethoxysilane through free radical polymerization result in fewer Si-O-Si three-dimensional networks. At the same time, the sulfur and nitrogen atoms in the thiazole ring have lone pairs of electrons and can form coordination bonds with the surface of the microspheres, significantly enhancing the interfacial binding force.

[0051] Comparative Example 7 is an anisotropic conductive adhesive film prepared by using the raw material composition, ratio and method of Example 22 of the Chinese invention patent with the publication number CN102136314A. It can be seen from the data in Table 1 that the tensile strength and the electrical conductivity are inferior to those of this application.

[0052] The above are only the preferred embodiments of the present invention and are not used to limit the present invention. However, for those of ordinary skill in the art, without departing from the scope of the technical solution of the present invention, any minor changes, modifications, and equivalent variations made using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any changes, modifications, and equivalent variations made to the above embodiments based on the essential technology of the present invention still fall within the protection scope of the technical solution of the present invention.

Claims

1. A composite microsphere, characterized in that, Prepared by the following method: (1) Under nitrogen protection, styrene monomer reacts to obtain monodisperse PS microspheres under the action of potassium persulfate and sodium dodecyl sulfonate; (2) Immerse the PS microspheres in concentrated sulfuric acid and stir for sulfonation, and then ultrasonically activate them with an amino silane coupling agent in absolute ethanol to obtain activated PS microspheres; (3) Mix an electroplating solution containing nickel sulfate, sodium hypophosphite, and sodium citrate with the activated PS microspheres and perform ultrasonic electroplating to obtain Ni@PS composite microspheres.

2. An anisotropic conductive film, characterized in that, Comprising the following raw materials in parts by weight: 60 - 80 parts of epoxy acrylate resin, 12 - 15 parts of modified adhesive, 10 - 30 parts of the composite microspheres of Claim 1, 1 - 3 parts of coupling agent, 0.5 - 1 part of modified dispersant, 10 - 30 parts of toluene; The modified adhesive is prepared by the following method: S1: Under nitrogen protection, 1,3 - bis((2,2 - dimethyl - 1,3 - dioxolan - 4 - yl)methoxy)propan - 2 - amine reacts with methacryloyl chloride under the action of triethylamine to form an amide product; S2: Pentaerythritol tetra(3 - mercaptopropionate) reacts with the amide product under the action of initiator AIBN to form an octa - arm cyclopentane compound, and the octa - arm cyclopentane compound hydrolyzes to form an octa - arm hydroxyl compound; S3: Cassava starch forms hydrolyzed starch under formic acid conditions, and then the hydrolyzed starch reacts with the octa - arm hydroxyl compound to form a modified adhesive.

3. The anisotropic conductive film according to claim 2, characterized in that, In step S1, the feeding mass ratio of 1,3 - bis((2,2 - dimethyl - 1,3 - dioxolan - 4 - yl)methoxy)propan - 2 - amine to methacryloyl chloride is 3:(10 - 12).

4. The anisotropic conductive film according to claim 2, wherein, In step S2, the feeding mass ratio of pentaerythritol tetra(3 - mercaptopropionate) to the amide product is 5:(12 - 16).

5. The anisotropic conductive film according to claim 2, wherein, In step S3, the feeding mass ratio of cassava starch to the octa - arm hydroxyl compound is (10 - 12):(6 - 8).

6. The anisotropic conductive film according to claim 2, characterized in that, The coupling agent is one of 3 - aminopropyltriethoxysilane and 3 - aminopropyltrimethoxysilane.

7. The anisotropic conductive film according to claim 2, characterized in that The modified dispersant is prepared by the following method: S1: Under nitrogen protection, slowly add 2 - amino - 4 - (4 - chlorophenyl)thiazole to a tetrahydrofuran solution of chloropropene magnesium and react for 4 - 8 h to obtain a double - bond compound; S2: Under nitrogen protection, 3 - glycidoxypropyltrimethoxysilane reacts with the double - bond compound to obtain a silylated product; S3: The silylated product, acrylic acid, and allyloxy polyoxyethylene ether react under the action of ammonium persulfate to form a modified dispersant.

8. The anisotropic conductive film according to claim 7, characterized in that, In step S1, the feeding molar ratio of chloropropene magnesium to 2 - amino - 4 - (4 - chlorophenyl)thiazole is (1.2 - 1.5):1; the concentration of the tetrahydrofuran solution of chloropropene magnesium is 0.5 mol / L.

9. The anisotropic conductive film according to claim 7, characterized in that, In step S2, the feeding mass ratio of 3 - glycidoxypropyltrimethoxysilane to the double - bond compound is (10 - 12):5; In step S3, the feeding mass ratio of the silylated product, acrylic acid, and allyloxy polyoxyethylene ether is 5:(10 - 15):(5 - 7).

10. A method for preparing an anisotropic conductive film according to any one of claims 2-9, characterized in that, Comprising the following steps: (1) Weigh by parts by weight: 60 - 80 parts of epoxy acrylate resin, 12 - 15 parts of modified adhesive, 10 - 30 parts of the composite microspheres of claim 1, 1 - 3 parts of coupling agent, 0.5 - 1 part of modified dispersant, and 10 - 30 parts of toluene; (2) Add the composite microspheres and the coupling agent into an anhydrous ethanol solution, ultrasonically disperse for 30 min, and vacuum dry at 60 °C for 2 h to obtain modified composite microspheres; Then, after successively performing high - speed shear mixing and grinding with a three - roll mill on the epoxy acrylate resin, modified adhesive, and toluene, add the modified composite microspheres and the modified dispersant, and mix evenly using a planetary stirrer to obtain a slurry; (3) Use a slot coater to evenly coat the slurry on a PET release film; pre - bake at 80 °C for 5 min to form a semi - cured film; place the semi - cured film in a vertical magnetic field to align the composite microspheres in the Z - axis direction; (4) Finally, perform step - wise curing: The first stage: cure at 100 °C for 30 min; the second stage: cure at 150 °C for 60 min. After curing, peel off the release film to obtain an anisotropic conductive film.

Citation Information

Patent Citations

  • Preparation method of composite microspheres, anisotropy conducting material and anisotropy conducting film

    CN102136314A